The knowledge worker and the projectified self: domesticating and disciplining creativity. (1st April 2017) - ,
Abstract : Since the 1970s, projects have become a widespread form of work and labour organisation. They represent complex temporary endeavours and suggest spontaneity and flexibility, albeit reliant on bureaucratic structures. In contrast to this, projects can also be seen as metaphors for late modern biographies and socialisation. Both notions directly affect knowledge work by domesticating knowledge and creativity to fit valorisation processes. Within obscured power relations, a subjectivising antinomy of predictability and flexibility arises: the projectified self. This form of subjectivity domesticates the knowledge worker contributing to new vulnerabilities to precarity due to flexible, spontaneous and uncertain biographies.